دور حصة التربية البدنية في ضبط حركة ونشاط الأطفال - عريق, لطيفة (جامعة الوادي - University of Eloued, 2020)
تهدف هذه الدراسة لمحاولة التعرف عن دور حصة التربية البدنية في ضبط حركة ونشاط الأطفال الذين يعانون من اضطراب عجز الانتباه المصحوب بفرط النشاط وفي زيادة تحصيلهم العلمي المدرسي فتم التطرق إلى كل من مفهوم صعوبات التعلم، عجز الانتباه، فرط النشاط، مفهوم التحصيل الدراسي وأهم أسبابه، وكذا ماهية اللعب وعلاقته بشخصية الطفل، وأخيرا حصة التربية البدنية والرياضية كطريقة لعلاج الأطفال الذين يعانون من ضعف الانتباه المصحوب بفرط النشاط. وقد توصلت الدراسة إلى أن الرياضة واللعب تعد أهم البرامج السلوكية التي تساعد المعلمين والأهل على مساعدة أبنائهم الذين يعانون من اضطراب عجز الانتباه المصحوب بفرط النشاط من أجل إفراغ الطاقة الزائدة وتوجيه سلوكهم ليكون مقبول اجتماعيا، وكذا زيادة تركيزهم وانتباههم للأمور المهمة في الحياة كالتعلم بمختلف أنواعه وزيادة تحصيلهم العلمي المدرسي عبر استغلال الألعاب الحركية والتعليمية التي تكون مناسبة لمثل هؤلاء الأطفال الذين يعانون من اضطراب عجز الانتباه المصحوب بفرط النشاط. Abstract: This study aims to try to identify the role of the share of physical eeducation in controlling the movement and activity of children who suffer from attention deficit coupled with overheating disorder and increase their academic achievement and its causes also the concept of play and its relation with personality of the child, and, finally, the share of physical education and sports as a way to treat children who suffer from attention deficit coupled with hyperactivity . The study found that sport and play is the most important behavioral programs that help teachers and parents to help their children who suffer from attention deficit coupled with overheating disorder for excess energy emptying and guide their behavior to be socially acceptable, as well as to increase their focus and their attention to the important things in life like learning and its different forms and to increase their education school through by the exploitation of the kinetic and educational games that would be appropriate for such children who suffer from attention deficit disorder coupled with overheating.
مقال
Keywords: اضطراب عجز الانتباه- التحصيل العلمي- الأطفال; Physical education; Child; disturbance; Attention deficit; Hyperactivity; School educational attainment.